2019
DOI: 10.3390/ijms20092340
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of C-Myc in Cancer Stem Cell-Related Signaling and Resistance to Cancer Chemotherapy: A Potential Therapeutic Target Against Colorectal Cancer

Abstract: Myc is a nuclear transcription factor that mainly regulates cell growth, cell cycle, metabolism, and survival. Myc family proteins contain c-Myc, n-Myc, and l-Myc. Among them, c-Myc can become a promising therapeutic target molecule in cancer. Cancer stem cells (CSCs) are known to be responsible for the therapeutic resistance. In the previous study, we demonstrated that c-Myc mediates drug resistance of colorectal CSCs using a patient-derived primary three-dimensional (3D) organoid culture. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(163 citation statements)
references
References 133 publications
5
157
0
1
Order By: Relevance
“…TaTDRL encodes a bHLH conserved domain at the C-terminal (295-344 aa), which localized to the nucleus and displayed transcriptional activation activity. MYC class transcription factors regulate genes involved in growth, cell cycle, signaling, and adhesion [19,20]. In generally, the carboxyl terminus of MYC family members contains a bHLH leucine zipper motif (bHLH-Zip), which has DNA-binding activity and is proposed to form homodimers or heterodimers with MYC-associated factor X (MAX) proteins via their bHLH domain [21,22].…”
Section: Structure and Localization Of The Tatdr-like Genementioning
confidence: 99%
“…TaTDRL encodes a bHLH conserved domain at the C-terminal (295-344 aa), which localized to the nucleus and displayed transcriptional activation activity. MYC class transcription factors regulate genes involved in growth, cell cycle, signaling, and adhesion [19,20]. In generally, the carboxyl terminus of MYC family members contains a bHLH leucine zipper motif (bHLH-Zip), which has DNA-binding activity and is proposed to form homodimers or heterodimers with MYC-associated factor X (MAX) proteins via their bHLH domain [21,22].…”
Section: Structure and Localization Of The Tatdr-like Genementioning
confidence: 99%
“…Molecular targeted therapies aimed at c‐Myc that interfere with c‐Myc synthesis, stability, and transcriptional activity have emerged as effective cancer treatments . It has been reported that c‐Myc could be regulated by CaMK II to facilitate cancer cell proliferation . Moreover, high expression of CaMK II was found in several cancers .…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been reported that c-Myc could be regulated by CaMK II to facilitate cancer cell proliferation. 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations